(untitled) (Journal of Social Sciences Review, 2023)
Exploring the teachers’ perception regarding implementation of quality assurance practices at university level was the aim of the in hand research. The main objective was knowing about teachers’ awareness regarding components of quality assurance and their implementation at departments level in university of the Punjab. It was descriptive research based on cross-sectional survey design in nature by applying quantitative research approach. Population for the present study was comprised all public universities which were situated in Pakistan. Data was gathered from 300 teachers who were working in 36 departments of University of the Punjab who selected by applying purposive sampling technique via self-developed questionnaire. The gathered data was arranged, coded and entered into computer for analysis. Data was analyzed with the help of SPSS (V.22) software by applying inferential and descriptive statistics. It was found that majority of the teachers were well aware about written mission statement, quality assurance office at department level, and quality assurance office at university components but minority of them were not aware about quality assurance policy, quality manual, and hold of self-assessment periodically. It is recommended that HEC should advise university to arrange extra seminars, conferences and workshops at department/ institution level to reassure involvement for good practice of teaching and quality assurance practices.